'A Note on Plywood from Nepal Asna' - Gupta, R. C.; Bist, B. S. (Indian Forester, 1980)
Nepal Asna (Terminalia alata var. nepalensis) was examined for its suitability for plywood. The note records the results of the experiments carried out.